ANALISIS SENYAWA ALKALOID DAUN TANAMAN JOHAR (Cassia siamea Lmk.) YANG BERPOTENSI SEBAGAI INSEKTISIDA PADA NYAMUK - Setiawan, Topan; Aminah, Sitti; Jura, Minarni R. (Jurnal Akademika Kimia, 2013)
Research about alkaloid compound of johar plant leaf (Cassia siamea Lmk.) which potential as insecticide at mosquito. The methods are used is laboratory experiment from johar plant leaf extract. Alkaloid has product from separated extract of johar plant leaf. Maximum wave has product by UV-Vis spectrophotometer is 306 nm. TLC product of johar plant leaf extracts are 2 components (Rf 0.89 and 0.91). TLC product of johar plant leaf alkaloid is 1 component (Rf 0.91). The product of HPLC showed 4 components for johar plant leaf and 2 components for alkaloid. The insecticide force of 25 mosquitos did by third for extract and alkaloid. The products are johar leaf extract have insecticide force for each treatment are 14, 10 and 14 mosquitos although alkaloids are 13, 8 and 2 mosquitos.